HUBUNGAN KONTROL DIRI DENGAN PERILAKU AGRESI VERBAL SISWA KELAS VII SMPN 174 JAKARTA - Habibah, Nabila Nurul; Marsinun, Rahmiwati (LPPM Institut Pendidikan Nusantara Global, 2023)
Adolescence is a period of searching for their identity or identity, and many are marked by things that lead to negative things such as tend to be unstable, have overflowing emotions, self-control scales and verbal aggression scales with data analysis techniques, namely product moment correlation. The results of data act impulsive, and also high aggressive behavior. The purpose of this study was to determine the relationship between self-control and verbal aggression of grade VII students of SMPN 174 Jakarta. This study used a correlational quantitative approach. The study population amounted to 120 students and the research sample was 92 students, the sampling technique is by simple random sampling. The instruments used are analysis showed a pearson correlation value of 0.609 with a level of sig. 0.001 (p< 0.05) which shows that the hypothesis is accepted so that there is a significant strong positive relationship between the self-control variable and the verbal aggression variable has a strong positive correlation.